Implementasi kebijakan dana desa untuk penanggulangan pandemi covid-19 di sampang - Hidayat, Endik (Universitas Dr.Soetomo, 2021)
The purpose of this article is to understand the implementation of village fund policies for the response to the Covid pandemic in Sampang Regency. The formulation of the problem is to find out what factors influence the success of programs funded by village funds in the midst of a pandemic in the Sampang case. The main theory used as an analysis is Edward III's policy implementation theory. This article uses a qualitative method with a case study research type. The data was collected using interview techniques and digital documents, online news, and the official website of the Sampang government. The results showed that the implementation of the village fund policy for the Covid-19 pandemic was going quite well. The factors that support the success of the communication dimension are the socialization of programs and information about the Covid-19 pandemic running optimally. Then another dimension, namely the bureaucratic structure, coordination between the implementers is quite intensive, the relationship that occurs is collaborative between policy actors or implementers. The inhibiting factor arises from the resource dimension due to the limited budget for village funds in dealing with Covid-19 in Sampang Regency so that infrastructure is not sufficient in order to prevent the spread of the corona virus.Keyword:Â Policy; Implementation; Pandemic; Covid-19.